Development and verification of lead-bismuth cooled fast reactor calculation code system Mosasaur - Zhang, Bin; Wang, Lianjie; Lou, Lei; Zhao, Chen; Peng, Xingjie; Yan, Mingyu; Xia, Bangyang; Zhang, Ce; Qiao, Liang; Wu, Qu (Frontiers in Energy Research, 2023)
Lead-bismuth cooled fast reactor calculation code system named MOSASAUR has been developed to meet the simulation requirements from LBFR engineering design. An overview of MOSASAUR developments is provided in this paper, four main functional modules and their models are introduced: cross-sections generation module, flux spectrum correction module, core simulation module and sensitivity and uncertainty analysis module. Verification and validation results of numerical benchmark calculations, code-to-code comparisons with the Monte-Carlo code and critical experimental calculations shown in this paper prove the capabilities of MOSASAUR in dealing with lead-bismuth cooled fast reactor analysis problems with good performances. Numerical results demonstrate that compared with the Monte-Carlo code, the relative errors of eigenvalues are smaller than 350pcm when the calculations were carried out with the same nuclear data file. Compared with the measured values, the errors will increase due to the simulation details and the measurement accuracy.